2009
DOI: 10.1007/s00520-008-0574-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intervention to prevent hypomagnesemia in cervical cancer patients receiving combination cisplatin and radiation treatment

Abstract: The increase of Mg(2+) to 2 g for the initial two cycles and then to 3 g with the third cycle of CisXRT therapy prevented episodes of CIH and decreased associated treatment delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…It has been reported that magnesium works as a cofactor for approximately 300 cellular enzymes concerning cellular energy metabolism involving ATP, muscle Na + /K + -pump activity, calcium channel activity, stabilization of membrane structures, and RNA/DNA polymerase [8][9][10][11][12]. Hypomagnesemia, which is defined as a serum magnesium level of less than 1.8 mg/dL [13], occurs in almost 90 % of patients receiving cisplatin chemotherapy [14]. It has been suggested that damage of renal tubular cells and Ca…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that magnesium works as a cofactor for approximately 300 cellular enzymes concerning cellular energy metabolism involving ATP, muscle Na + /K + -pump activity, calcium channel activity, stabilization of membrane structures, and RNA/DNA polymerase [8][9][10][11][12]. Hypomagnesemia, which is defined as a serum magnesium level of less than 1.8 mg/dL [13], occurs in almost 90 % of patients receiving cisplatin chemotherapy [14]. It has been suggested that damage of renal tubular cells and Ca…”
Section: Introductionmentioning
confidence: 99%
“…Hunter, et al 7 estudiaron en más de 200 pacientes el efecto beneficioso de la suplementación con sulfato de magnesio en los pacientes en tratamiento combinado con cisplatino y radioterapia. Además, observaron que los pacientes con diabetes mellitus o con hipertensión eran los que tenían más riesgo de sufrir déficit de magnesio, debido a problemas renales.…”
Section: Discussionunclassified
“…Hunter, et al 7 studied the beneficial effect of magnesium sulfate supplementation in more than 200 patients on cisplatin and radiotherapy combined treatment. In addition, they reported that patients with diabetes mellitus and/or hypertension were at higher risk of developing magnesium deficiency, owing to renal problems.…”
Section: Discussionmentioning
confidence: 99%